DIRECTIONS FOR IMPROVEMENT OF THE PENSION SYSTEM OF THE REPUBLIC OF UZBEKISTAN - Samieva Gulnoza , Tokhirovna (THE INNOVATION ECONOMY, 2025)
This article is devoted to the topic of improving the pension system in the Republic of Uzbekistan, and its main content is focused on the analysis of the pension and benefit reform in Uzbekistan. This article reflects the fact that payments made to citizens by the state or other entities in cases established by law, that is, in the form of pensions and benefits, are regular and, as a rule, lifelong. The article examines measures related to the scientific solution to the problem of rigid distribution of funds and the emergence of a deficit in pension systems due to the increase in life expectancy of pensioners, studied based on the experience of most countries. The article examines the improvement of the scientific and conceptual foundations of reforming the pension system, including such areas as the introduction of a minimum pension that can ensure the standard of living of a pensioner, ensuring a direct link between contributions paid during the period of work and the amount of the pension, as well as stratification of sources of financing pension payments. Another important goal of the pension system is the social protection of needy segments of the population, including the elderly, disabled people, people who have lost their breadwinner, as well as strengthening state support and incentives, further improving the social protection of other needy categories of the population, and the author partially touched upon these issues in the article.